Perceptions and practices of curriculum development in the south African Universities of Technology - Mkhize, Dumisani Ezra (South African Journal of Higher Education, 2016)
This study was undertaken to arrive at the appropriate perspective on how both academic staff and students at Universities perceive Curriculum development. It is of vital significance that students and academic staff have a common understanding of what should be contained in the curriculum since the two parties (academic staff and students) are co-partners in education. Amongst others, the study aims to investigate ways of developing and aligning the existent curriculum to the global needs.